Financial Implications to Medicare from Changing the Dialysis Modality Mix under the Bundled Prospective Payment System. Issue 7 (November 2014) - Liu, Frank X.; Walton, Surrey M.; Leipold, Robert; Isbell, Deborah; Golper, Thomas A.
Background: The economic burden of treating end-stage renal disease (ESRD) continues to grow. As one response, effective January 1, 2011, Medicare implemented a bundled prospective payment system (PPS, including injectable drugs) for dialysis patients. This study investigated the 5-year budget impact on Medicare under the new PPS of changes in the distribution of patients undergoing peritoneal dialysis (PD), in-center hemodialysis (ICHD), and home hemodialysis (HHD). Methods: An Excel-based budget impact model was created to assess dialysis-associated Medicare costs. The model accounted for dialysis access establishment, the current monthly capitation physician payment for ESRD, Medicare dialysis payments (including start-up costs), training, oral drug costs, and the costs and probabilities of adverse events including access failure, hospitalization for access infection, pneumonia, septicemia, and cardiovascular events. United States Renal Data System (USRDS) data were used to project the US Medicare dialysis patient population across time. The baseline scenario assumed a stable distribution of PD (7.7%), HHD (1.3%) and ICHD (91.0%) over 5 years. Three comparison scenarios raised the proportions of PD and HHD by (1 ) 1% and 0.5%, (2 ) 2% and 0.75%, and (3 ) 3% and 1% each year; a fourth scenario held HHD constant and lowered PD by 1% per year. Results: Under the bundled PPS, scenarios that increased PD and HHD from 7.7% and 1.3% over 5 years resulted in cumulative savings to Medicare of $114.8M (Scenario 1, 11.7% PD and 3.3% HHD at year 5), $232.9M (Scenario 2, 15.7% PD and 4.3% HHD at year 5), and $350.9M (Scenario 3, 19.7% PD and 5.3% HHD at year 5). When the PD population was decreased from 7.7% in 2013 to 3.7% by 2017 with a constant HHD population, the total Medicare payment for dialysis patients increased by over $121.2M. Conclusions: Under Medicare bundled PPS, increasing the proportion of patients on PD and HHD vs ICHD could generate substantial savings in dialysis-associated costs to Medicare.